De oplossing van de "Werkmansbode", de "Nederlander" en de "Radicale Hervorming" in de "Vooruitgang" - Braakensiek, Johan, (1897)
De oplossing van de "Werkmansbode", de "Nederlander" en de "Radicale Hervorming" in de "Vooruitgang"